Pengaruh Senam Hamil Terhadap Penurunan Nyeri Punggung Bawah Pada Ibu Hamil Trimester II Di Puskesmas Sonomartani Kec. Kualuh Hulu Kab. Labuhanbatu Utara Tahun 2022 - Meydriana Theodora; Eka Purnama; Siska Suci Triana Ginting; Ester Simanullang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Pregnancy is a continuous chain and starts from ovulation, release of ovum, migration of spermatozoa and ovum, conception process, nidation (implantation) of the endometrium, formation of the placenta and growth and development of the products of conception for approximately 280 days (40 weeks) and no more of 300 days (43 weeks). The length of pregnancy from ovulation to parturition is approximately 280 days (40 weeks) (Rukiah & Yulianti, 2014). The aim of this study was to determine the effect of pregnancy exercise on reducing lower back pain in second trimester pregnant women at the Sonomartani District Health Center. Kualuh Hulu District. North Labuhanbatu in 2022”. Experimental type of research. Experimental research is a research design used to look for causal relationships with the involvement of research in manipulating independent variables (Nursalam, 2019). The sample in this study were all second and third trimester pregnant women at the Sonomartani District Health Center. Kualuh Hulu District. North Labuhanbatu in 2022 there will be 35 people. . The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square. The results of the tabulation research show a relationship between the duration of using injectable contraceptives for 3 months and menstrual disorders in 3-month injectable contraceptive acceptors at the Melak District Health Center. West Kutai, East Kalimantan in 2023 with a p-value = 0.049. So Ho is rejected and Ha is accepted, which means there is a relationship between the length of use of 3-month injectable contraceptives and menstrual disorders in 3-month injectable contraceptive acceptors at the Melak District Health Center. West Kutai, East Kalimantan in 2023. Conclusion: Family planning acceptors can choose the right contraceptive method. Family planning acceptors can tell midwives or health workers about the various types of contraceptives before choosing the contraceptive method. Always monitor changes in side effects so that if there are complaints they can be addressed immediately.